Hanging: A Ten-Year Retrospective Review of Malaysian Forensic Cases - Naziri, SZM; Abu Bakar, SN; Alias, A; Ibrahim, A; Swarhib, DMJM; Nor, FM (Int Islamic Univ Malaysia, Kulliyyah Medicine, 2024)
Indexed by WOS/ Scopus